2018
DOI: 10.21037/jtd.2018.06.108
|View full text |Cite
|
Sign up to set email alerts
|

Relation between changes in red blood cell distribution width after coronary artery bypass grafting and early postoperative morbidity

Abstract: ΔRDW was identified to be an independent predictor of early adverse events, and a ΔRDW cut-off of 1.45 was found to predict early adverse events after CABG. Careful monitoring of RDW trends after isolated CABG provides a simple, inexpensive and objective means of predicting early adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 28 publications
2
13
1
1
Order By: Relevance
“…Even more importantly, we observed for the very first time that the in-hospital variation of RDW (i.e., the ratio between RDW values measured at hospital admission and discharge) was a significant predictor of early adverse outcomes, wherein patients with a delta RDW >1 had 60% and 88% enhanced risk of developing 1-month PTA-related complications and early restenosis after hospital discharge, respectively. This finding is in accordance with previous evidence garnered from other cardiovascular disorders, and showing that in-hospital variation of RDW may be a useful predictor of mortality in patients with heart failure (19, 20), higher readmission or unexpected death in the intensive care unit (ICU) (21), but also significantly predicted early adverse events after CABG (7). This would lead us to conclude that routine calculation of delta RDW between values measured at hospital admission and discharge may be a valuable approach in all patients undergoing PTA, wherein those exhibiting an increase during hospital stay should then be more strictly monitored during follow-up, or even subjected to more aggressive pharmacological or behavioral management (e.g., enhanced burdens of physical exercise).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Even more importantly, we observed for the very first time that the in-hospital variation of RDW (i.e., the ratio between RDW values measured at hospital admission and discharge) was a significant predictor of early adverse outcomes, wherein patients with a delta RDW >1 had 60% and 88% enhanced risk of developing 1-month PTA-related complications and early restenosis after hospital discharge, respectively. This finding is in accordance with previous evidence garnered from other cardiovascular disorders, and showing that in-hospital variation of RDW may be a useful predictor of mortality in patients with heart failure (19, 20), higher readmission or unexpected death in the intensive care unit (ICU) (21), but also significantly predicted early adverse events after CABG (7). This would lead us to conclude that routine calculation of delta RDW between values measured at hospital admission and discharge may be a valuable approach in all patients undergoing PTA, wherein those exhibiting an increase during hospital stay should then be more strictly monitored during follow-up, or even subjected to more aggressive pharmacological or behavioral management (e.g., enhanced burdens of physical exercise).…”
Section: Discussionsupporting
confidence: 91%
“…Several lines of evidence now attest that enhanced anysocytosis is commonplace in patients with a large number of human pathologies, including cardiovascular disorders (10), and that increased RDW values also reliably predict morbidity, hospital readmission and death (11, 12). Although several previous studies showed that anysocytosis may be associated with adverse outcome in patients undergoing CABG, percutaneous coronary angioplasty (PCA), percutaneous coronary intervention (PCI) and even postinterventional thrombolysis for acute coronary syndrome (7, 13, 14, 15, 16, 17, 18), no information has been published to best of our knowledge on its diagnostic efficiency for predicting complications or adverse outcomes in patients undergoing PTA for severe forms of PAOD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the parameters obtained from routine blood tests, which may be of prognostic value. For example, the effects of changes in red blood cell distribution (RDW) on mortality after CABG operations were investigated by Lee et al, and DeltaRDW value was determined as an independent predictor in predicting early postoperative adverse events in multivariate analysis [Lee 2018]. DeltaNLR value has recently been investigated in various fields of medicine in this respect.…”
Section: E198mentioning
confidence: 99%
“…p<0.05 olması istatistiksel olarak anlamlı değer olarak kaydedilmiştir. İnme, koroner arter hastalığı gibi birçok hastalıkta RDW artışı literatürde tanımlanmıştır17,18 .Ayrıca RDW'nin çoklu kardiyovasküler hastalıkların mortalitesinde önemli bir biyobelirteç olduğu bildirilmiştir19 . 25992 kişinin dahil edildiği çalışmada klasik risk faktörlerinden bağımsız olarak inme için RDW'nin bir parametre olduğu tespit edilmiştir20 .…”
unclassified